Namibia doubles pearl millet yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Most Namibians eat mahangu, a coarse cereal prepared from pearl millet. But despite its being a staple, no research was done on this crop in Namibia before Independence in 1990. For most Namibians, the basic choice of food is between the flour of...